Government expenditure components that affects economic growth in Malaysia - M Ram Lee, Nuraida Idora (2018)
This study is an effort to investigate the government expenditure components that affects economic growth in Malaysia for a period of 30 years from year 1987 to 2016. There were four government expenditure components had been listed which are Education Expenditure (ED), Health Expenditure (HE), Defense and Security Expenditure (DS) and last but not least Social Services Expenditure (SS) as independent variables and Economic Growth (GDP) as dependent variable. This study used 30 secondary data for each variables from year 1987 to 2016 on yearly basis. This study used Eviews9 software as a statistical tool for the purpose of the data analysis. All of the results obtained portrayed all of the variables which are ED, HE, DS and SS towards GDP. This study would be beneficial to the researcher, to the public, and policy makers in order for them to shape the future of a country without wasting any resources.